Maxillary sinus lifting with minimally invasive technique (Research, Society and Development, 2024)
In edentulism, it is common for the maxillary region to have low bone density, due to the pneumatization of the maxillary sinus and the reabsorption that occurs in the alveolar bone over time. Some techniques are mentioned in the literature, which enable patient rehabilitation and facilitate the insertion of titanium implants. The Summers technique (performed through the alveolar crest with osteotomes) and the Caldwell Luc approach technique (performed from the side with rotating instruments) can be mentioned. This research aimed to select a method chosen as a reference, among the types of existing techniques to gain bone height and, consequently, present success in the installation of implants in the maxillary region. 24 patients were selected, of whom 26 maxillary sinuses were operated on and 35 accesses to the maxillary sinus were performed. In the research, there were 3 ruptures of the sinus membrane, which were not included in the analysis, and only one case did not achieve a satisfactory result in bone height gain. The average height gain was 5.7mm. The technique chosen and performed with rotating instruments, through the bone edge, proved to be safe achieving significant height gain and enabling the prosthetic rehabilitation of patients. Furthermore, patients experienced minimal discomfort during and after surgery.